“The Good Years Have Passed and Will Never Come Again”: Political Functions of Nostalgic Fantasies in Incel Discussions - Emilia Lounela; Shane Murphy; Ümit Bedretdin (Social Media + Society)
This study unpacks the implicit and explicit political functions nostalgia takes in incel discussions on the past on the incels.is forum. By combining a discourse theoretical approach with the theoretical framework of fantasy, the study demonstrates how an imagined ideal past is used to construct community and collective identity in an incel-specific, antagonistic way. Nostalgic fantasies articulated on incels.is often evoke a lost utopia, an inevitable dystopian future, and an enemy—usually women and feminism—responsible for this development. The unattainable nature of fantasy continuously feeds attachment to community and works to construct inceldom as a political identity. The study suggests that the dynamics and function of nostalgic narratives in incel discourse differ significantly from far-right nostalgia despite thematic similarities. Acknowledging this difference is crucial in understanding the political implications of nostalgia in incel online communities. This article therefore introduces the concept of incel nostalgia to describe the specific way the past is used to construct and justify incel ideology.